Pouch of sorrow: Undiagnosed isthmocele – presenting as secondary infertility of 11 years in a middle age female (Indian Journal of Case Reports, 2024)
In the past decade, the rate of cesarean sections has doubled leading to the more frequent occurrence of cesarean-related complications. Cesarean scar site diverticulum or isthmocele is one such complication that is defined as an outpouching of the anterior uterine wall at the cesarean scar site in continuity with the endometrial cavity, creating a wedge-shaped defect of variable depth. We report a case of a middle-aged female with secondary infertility for the last 11 years with one live issue 12 years back through a cesarean section at term. She had undergone an array of investigations for infertility for the past 5 years. She was diagnosed as having an isthmocele and managed with surgical repair of the defect at our hospital with subsequent assisted conception 8-month post-surgical repair. The importance of diagnosing a cesarean scar diverticulum cannot be understated not only because it is a surgically treatable cause of infertility but also because if such patients conceive, they may land in uterine rupture, placenta accreta, or scar ectopic pregnancy which can complicate into life-threatening situations.